Traverse. - Lee, Jolly Yu See. (2013)
This report provides an insight to the creative process of a free floating experiential game named Traverse. Being an aesthetically driven game, it will be important to note that there were specific design choices made to aid this intention. Mood and emotion became the main focus during the conceptual stages.